Online Learning Models during the COVID-19 Pandemic: A Bibliometric Analysis - Nugroho Nugroho (Jurnal Basicedu, 2023)
Online learning as a method of avoiding the spread of COVID-19 adds a new dimension to the fight against this virus. The first publication with online learning as a topic can be traced back to  1986, An Algorithm for Learning Without External Supervision and Its Application to Learning Control Systems (Nikolić & Fu, 1986). Online learning in the education sector has become increasingly prominent in recent years. The study aims to discover and illustrate the direction of trend development of research on online learning during COVID-19. The study used the bibliometric analysis method. It examined 1,594 scientific articles from 159 authors across 110 countries and 160 affiliations. The information gathered between 2019 and 2021 was relevant to the topic. To visualize the result of the study, the researcher used the VOSViewer application. The study shows that research on online learning during the COVID-19 pandemic increased consistently from 2019 to 2021. This study found 1249 documents in that period. Yang H is the most co-authored author. While the most prolific writer is Hong J.C, with 8 articles. This systematic field mapping helps in graphically depicting the evolution of publications as well as identifying areas of current research interest and future research potential. These findings provide a solid basis for future research in this area.